Regular Expression Recipes for Windows Developers : A Problem-Solution Approach - Good, Nathan A (Apress, 2013)
This book contains recipes for regular expressions that you can use in languages common on the Microsoft Windows platform. It provides ready-to-go, real-world implementations and explains each recipe. The approach is right to the point, so it will get you off and using regular expressions quickly.